1985
DOI: 10.1073/pnas.82.13.4535
|View full text |Cite
|
Sign up to set email alerts
|

Alpha and beta human transforming growth factors stimulate prostaglandin production and bone resorption in cultured mouse calvaria.

Abstract: Human a and /3 transforming growth factors (TGF-a and TGF-/8) stimulated the production of prostaglandin E2 (PGE2) and bone resorption in neonatal mouse calvaria in organ culture. Significant stimulation of bone resorption by TGF-a was observed with a concentration of 0.2 ng/ml (35 pM) and by TGF-.6 with 0.2 ng/ml (8.0 pM).Enhanced production of PGE2 and bone resorption stimulated by either TGF-a or TGF-.8 were both inhibited by indomethacin. We conclude that TGF-a and TGF-.8 are potent and powerful stimulator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
91
2

Year Published

1987
1987
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 334 publications
(95 citation statements)
references
References 28 publications
2
91
2
Order By: Relevance
“…In addition, the ability of TGFa and EGF to indirectly stimulate bone-resorbing activity has long been described (Tashjian et al 1985, Ibbotson et al 1986. Several previous studies have also shown expression of EGFR in BMSCs and in osteoblast-like cells, as well as biological effects of EGF and/or TGFa in osteoblasts (Ibbotson et al 1986, Drake et al 1994, Sodek et al 1995, Satomura et al 1998.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the ability of TGFa and EGF to indirectly stimulate bone-resorbing activity has long been described (Tashjian et al 1985, Ibbotson et al 1986. Several previous studies have also shown expression of EGFR in BMSCs and in osteoblast-like cells, as well as biological effects of EGF and/or TGFa in osteoblasts (Ibbotson et al 1986, Drake et al 1994, Sodek et al 1995, Satomura et al 1998.…”
Section: Discussionmentioning
confidence: 99%
“…The increased potency of milrinone in mouse calvaria compared with the fetal rat limb bones may be explained as a result of the effect being mediated by prostaglandin production in the calvaria. Several agents, including epidermal growth factor (18,19), transforming growth factor (20,21), potassium (15), and thrombin (13), whose effect on bone resorption is mediated by endogenous prostaglandin production exhibit different potencies in limb bones and calvaria.…”
Section: Discussionmentioning
confidence: 99%
“…The relative composition of bone is presented in the Table 1, while the most important biomedical properties of the bones are presented in Table2. The in vivo bone biosynthesis is controlled by many factors such as: BMP (bone morphogenetic proteins) (Abe et al 2000), transforming growth factors (Tashjian et al 1985), cytokines (de Vernejoul et al 1993 ), hormones (Bollerslev et al 1991 ; www.intechopen.com Advances in Collagen/Hydroxyapatite Composite Materials 5 1990; Hock and Gera 1992), transcription factors Ogawa et al 2000), adhesion molecules (Miyake et al 1991) and so on.…”
mentioning
confidence: 99%